Uncovering the Latent Drivers of Risk Management System Adoption in Indonesian Small and Medium Enterprises - Aries Heru Prasetyo; William Ben Gunawan (AIBPM Publisher, 2026)
Research on family firm SMEs has predominantly emphasized risk-taking behavior as a driver of performance, while limited attention has been given to the determinants of risk management system adoption. Aiming to address the gap, this study tries to identify the latent drivers motivating Indonesian family firm SMEs to adopt risk management practices. Using survey data from 233 firms and applying principal component analysis (PCA), the study extracts underlying motivational factors from validated questionnaire items. The results reveal seven key determinants: knowledge, accounting, good governance, sustainability, value, obligatory, and personal motivations. The Kaiser-Meyer-Olkin (KMO) value of 0.766 and significant Bartlett’s test confirm sampling adequacy, while all extracted factors show eigenvalues greater than one. These determinants collectively explain a substantial proportion of variance and indicate that both cognitive (knowledge-based) and behavioral (owner-driven) considerations influence adoption decisions. The study finds that family firm SMEs are not purely intuition-driven, but increasingly use structured, evidence-based practices. However, the results are limited to the Indonesian context and an exploratory use of PCA. Future research should use confirmatory methods and cross-country comparisons to enhance generalizability.